IMPLIMENTATION OF INTELLIGENT CAP WITH DROWSY DETEC TION AND VEHICLE MONITORING - Sushma Telrandhe; Darshana Nimje; Rohit Nitnaware (International Journal of Innovations in Engineering Research and Technology, 2021)
Drowsiness”, a state which is often seen in drivers now-a-days has become a serious issue in road mishaps. Driver fatigue resulting from sleep deprivation or s leep disorders is an important factor in the increasing number of accidents. The development of technology for preve nting drowsiness at the wheel is a major challenge in the field of accident avoidance system. . Sleepy drivers often do not take correct action prior to a collision.